PET-CR as a potential surrogate endpoint in untreated DLBCL: meta-analysis and implications for clinical trial design. Issue 12 (15th October 2022) - Broglio, Kristine; Kostakoglu, Lale; Ward, Carol; Mattiello, Federico; Sahin, Denis; Nielsen, Tina; McGlothlin, Anna; Elliott, Corrine F.; Witzig, Thomas; Sehn, Laurie H.; Trnĕný, Marek; Vitolo, Umberto; et al.
Abstract: This study's focus is the association of end-of-therapy (EOT) PET results with progression-free (PFS) and overall survival (OS) in patients with diffuse large B-cell lymphoma receiving first-line chemoimmunotherapy. We develop a Bayesian hierarchical model for predicting PFS and OS from EOT PET-complete response (PET-CR) using a literature-based meta-analysis of 20 treatment arms and a substudy of 4 treatment arms in 3 clinical trials for which we have patient-level data. The PET-CR rate in our substudy was 72%. The modeled estimates for hazard ratio (PET-CR/non-PET-CR) were 0.13 for PFS (95% CI 0.10, 0.16) and 0.10 for OS (CI 0.07, 0.12). Hazard ratios varied little by patient subtype and were confirmed by the overall meta-analysis. We link these findings to designing future clinical trials and show how our model can be used in adapting the sample size of a trial to accumulating results regarding treatment benefits on PET-CR and a survival endpoint.